ANALYSIS OF THE EFFECT OF KETAPANG LEAF EXTRACT (Terminalia catappa) ON THE GROWTH AND PROFILE OF BACTERIA IN THE MAINTENANCE OF INDIAN BOTIA FISH LARVAE (Botia lohachata) (Journal of Fish Nutrition, 2025)
This study aimed to evaluate the potential of ketapang leaf extract (Terminalia catappa) as an agent to enhance the survival and growth of Botia india (Botia lohachata) larvae, as well as its effect on the bacterial profile in the rearing medium. The experiment was conducted using a Completely Randomized Design (CRD) with five different treatment doses of ketapang leaf extract, namely 0 g/L (control), 0.3 g/L, 0.6 g/L, 0.9 g/L, and 1.2 g/L, each replicated three times. The observed parameters included survival rate, growth (absolute weight and absolute length), and the total bacterial count in the rearing medium. The results showed that the administration of ketapang leaf extract had a significant effect (p
Keywords: aquaculture, bacteria, Botia lohachata, larvae, growth, survival Terminalia catappa